Obligations and Behaviors That Impact Sleep in Prelicensure Baccalaureate Nursing Students. Issue 1 (January 2022) - Blome, Melissa; Johnson, Michelle; Beck, Mark; Jones, Mark
Abstract : Background: Nursing students have obligations and behaviors that impact sleep. Purpose: The purpose of this study was to investigate sleep among prelicensure baccalaureate nursing students and describe factors that impact their sleep quality and daytime sleepiness. Methods: Prelicensure nursing students (n = 254) completed questionnaires that included demographics; obligations and behaviors that always, sometimes, or never caused sleep loss on a daily or weekly basis; the Pittsburgh Sleep Quality Index; the Epworth Sleepiness Scale; and the Sleep Hygiene Index. Results: College classes were the most frequent reason why participants always lost sleep. Obligations of work, classes, and technology use into the night significantly predicted sleep hygiene; obligations of work, family, activity with friends, and classes significantly predicted sleep quality. Conclusion: There is a need for education about behaviors and obligations that impact sleep in undergraduate nursing students, along with resources to assist in coping with external stressors. Abstract : Supplemental digital content is available in the text.